Bank interest rate margin, portfolio composition and institutional constraints - Li Xian Liu; Milind Sathye (Journal of Risk and Financial Management, 2019)
This study empirically examines how the bank specific factors, macro-economic, and institutional variables impact interest margins in China's banking sector. A panel data analysis of bank data for the period 1988-2015 was carried out. We found a significant association between credit quality, risk aversion, liquidity risk, and the proportion of corporate and industrial loans and the adjusted interest spread (AIS). GDP growth rate, inflation, and the proportion of national savings to the GDP were found to have significant association with the AIS. Furthermore, institutional variables were found to have a significant moderating effect on the AIS. We contribute to the literature by examining a unique context and a more accurate measure of bank interest margin not used in prior studies.
Keywords: 330; adjusted interest spread; corporate and industrial loans; financial freedom; monetary freedom; government spending; economic freedom